2017
DOI: 10.1007/s10964-017-0769-2
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Relations between Social Identity and Prosocial and Antisocial Behavior in Competitive Youth Sport

Abstract: The social identities formed through membership on extracurricular activity groups may contribute to the frequency with which youth engage in prosocial and antisocial behavior. However, researchers have yet to disentangle the individual- and group-level processes social identification effects operate through; sex and perceived norms may also moderate such effects. Thus, we investigated the hierarchical and conditional relations between three dimensions of social identity (i.e., ingroup ties, cognitive centrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 88 publications
1
24
0
1
Order By: Relevance
“…The latter was most frequent when participants experienced high antisocial combined with low prosocial behaviour from their teammates. In other work, athletes who perceived that their teammates engaged in more antisocial behaviours toward one another during practices, also reported more antisocial behaviour toward their teammates (Benson, Bruner, & Eys, 2017;Bruner et al, 2018).…”
Section: Positive Predictors Of Antisocial Behaviourmentioning
confidence: 92%
See 1 more Smart Citation
“…The latter was most frequent when participants experienced high antisocial combined with low prosocial behaviour from their teammates. In other work, athletes who perceived that their teammates engaged in more antisocial behaviours toward one another during practices, also reported more antisocial behaviour toward their teammates (Benson, Bruner, & Eys, 2017;Bruner et al, 2018).…”
Section: Positive Predictors Of Antisocial Behaviourmentioning
confidence: 92%
“…More recent research has identified variables that are linked only to teammate behaviour, for example descriptive norms and social identity (e.g. Bruner et al, 2018). Descriptive norms refer to the degree to which one's teammates act prosocially (or antisocially) toward other members of their team.…”
Section: Prosocial Behaviourmentioning
confidence: 99%
“…Taking the distinction of affective dimensions, several studies have related them to aspects that are part of the psychological and emotional wellbeing of humans [5][6][7], such as life satisfaction, perfectionism or emotional intelligence, among others [8][9][10][11][12][13]. However, due to the fact that current research has identified that the associations of the TME do not consistently fit with all anxiety disorders and clinicians are working on improving the use of the model [14], the number of studies that analyze the relation between affect and social anxiety has increased during the last years.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the result is aggressive and violent behavior, an excessive desire to win, and other socially undesirable qualities [3]. For this reason, Kavussanu and Boardley [2] created the Scale of Prosocial and Antisocial Behavior in Sports to measure such behaviors in the sports context, a scale that has been successfully applied in multiple studies [4,5]. In the Spanish context, there are currently no instruments for assessing prosocial and antisocial behavior in sport.…”
Section: Introductionmentioning
confidence: 99%